Phytochemical Heterocycles in Depression Management: A Sustainable Strategy - Kaur, Harmanbir; Kaur, Tejinder (Scripta Medica, 2026)
According to WHO, depression is raising globally and expected as global burden by 2030. After COVID-19, drastic incline led to 17 % of total world population that suffered from well-known mental disorder depression and around 140,000 suicides annually attributed to depression. Owing to the diverse adverse effects associated with marketed antidepressants, research has increasingly shifted towards traditional herbal medicines for curing the both physical and emotional symptoms associated with depression. In recent years, natural products, particularly plant-derived secondary metabolites have with heterocyclic backbones, has become promising candidates for depression therapy. This review explores the medicinal potential of various plant-based compounds, including indole alkaloid, pyridine alkaloid, saponins, polyphenols. The secondary metabolites of these plants have demonstrated markable antidepressant-like effects in preclinical studies by modulating neurotransmitter system, reducing inflammation and promoting neurogenesis. For instance, compounds such as psychollatine and mitragynine (indole alkaloid), saikosaponin (saponins) and polyphenolic compounds like crocin and curcumin have resultant biological activity. Herbal remedies like St John’s Wort (Hypericum perforatum), saffron, turmeric and ginseng have been used from centuries for mood regulation. By combining traditional knowledge with modern scientific researches, researchers can utilise the nature’s therapeutic power to innovate safer and effective treatments for depression. However, further investigation is necessary to elucidate the accurate mechanism of these compounds through which they exert their effect, optimise dosing, quality control and rigorous clinical trials. Ultimately, by combining the best of both traditional medicine and modern science- there can be revolution in the treatment of depression and lives of countless individuals can be improved.
Keywords: CNS; Depression; Antidepressive agents; Heterocyclic compounds; Secondary metabolites, plant